The Effect of Effective Microorganisms on the Quality of Sambar Deer (Cervus unicolor) and Goat Feces Compost Mixed with Kumpai Grass (Hymenachne amplexicaulis (Rudge) Nees.): Pengaruh Pemberian Effective Microorganism Terhadap Kualitas Kompos Feses Rusa Sambar (Cervus unicolor) dan Kambing dengan Campuran Rumput Kumpai (Hymenachne amplexicaulis (Rudge) Nees.) - Siti Ma'rifah; Satrio Wibowo; Heri Sujoko; Okta Mahesa Putra; Annas Puji Yulianto (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2026)
Compost is an organic fertilizer produced through the fermentation of solid and liquid animal wastes (urine) that contains essential macronutrients such as nitrogen (N), phosphorus (P), and potassium (K), as well as micronutrients including calcium (Ca), magnesium (Mg), and sulfur (S). In general, fertilization is applied to the soil using inorganic fertilizers, green manure, and compost to improve the physical, chemical, and biological properties of the soil. The application of compost contributes to nutrient availability and enhances soil structure and microbial activity. The feces of sambar deer (Cervus unicolor) have textural characteristics similar to goat manure but generally exhibit a higher C/N ratio (>35), whereas goat manure typically has a C/N ratio above 30. Therefore, a combination of deer and goat feces with the addition of effective microorganisms (EM) is expected to reduce the C/N ratio and improve the nutrient quality of compost. The data were analyzed using analysis of variance (ANOVA), and when significant or highly significant differences were observed, further analysis was conducted using the Honestly Significant Difference (HSD) test. The results showed that each treatment had a significant effect (p<0.05) on increasing pH, moisture content, total N, organic C, C/N ratio, and P and K contents. All compost quality parameters met the compost standards according to SNI 19-7030-2004. Keywords: effective microorganisms, goat, compost fertilizer, sambar deer